Planning for a night out : local governance, power and night-time in Christchurch, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Resource and Environmental Planning at Massey University, Turitea, Aotearoa, New Zealand - Johnston, Karen Marie (Massey University, 2014)
This research explores the changing nature of local governance and how power is exercised within Christchurch City Council’s decision-making process of its revitalisation of the Central Business District (CBD). A governmentality theoretical framework extends the scholarly debate on local government decision-making and allows for the exploration of social relations and lived realities of young people who use the night-time spaces created by the CBD revitalisation process. Three research questions structure the thesis: how is power exercised during CBD decision-making processes within Christchurch City Council?; what governmental technologies are adopted by Christchurch City Council to revitalise the CBD between 1999 and 2010?; and, what are the lived realities of the young people who use the revitalised spaces of the CBD? Christchurch, New Zealand’s second largest city, is the case study because of its recent CBD revitalisation and the significant changes to its decision-making processes. These changes impact on the way revitalisation is executed. The decision-making process of CBD revitalisation is examined through a qualitative methodology. Methods involved: document analysis; observations; individual, semi-structured interviews (with elected and non-elected local government representatives, business people, and police); and, focus-group interviews with young people who enjoy the CBD night-time entertainment spaces. There are three key research findings. First, power is simultaneously dispersed to an outside organisation and concentrated within the Council in fewer people. Particular actors have significant influence over decision-making. Second, governing at a distance occurs using technologies of a key stakeholder group followed by changes to internal Council decision-making. A post-political turn emerged where consensus is encouraged and political dissent discouraged. Third, the revitalisation project is successful in the creation of a vibrant night-time economy where young people drink and socialise. Paradoxically, these new subjects are constituted through the revitalised spaces as a problem, bringing into stark relief the conflicts between public and private interests in Christchurch’s CBD revitalisation. This research offers new possibilities for planning scholars. Governmentality allows for the critical examination of power in local governance with the explicit inclusion of the lived realities of the subjects of that governance.
Keywords: City planning; Urban renewal; Nightlife; Night life; Central business district; Christchurch; New Zealand